The Connexin50D47A Mutant Causes Cataracts by Calcium Precipitation - Berthoud, Viviana M. (Invest Ophthalmol Vis Sci, 2019)
PURPOSE: Mutations in connexin50 (Cx50) and connexin46 (Cx46) cause cataracts. Because the expression of Cx46fs380 leads to decreased gap junctional coupling and formation of calcium precipitates, we studied Cx50D47A lenses to test whether Cx50 mutants also cause cataracts due to calcium precipitation. METHODS: Connexin levels were determined by immunoblotting. Gap junctional coupling conductance was calculated from intracellular impedance studies of intact lenses. Intracellular hydrostatic pressure was measured using a microelectrode/manometer system. Intracellular free calcium ion concentrations ([Ca(2+)](i)) were measured using Fura-2 and fluorescence imaging. Calcium precipitation was assessed by Alizarin red staining and compared to the distribution of opacities in darkfield images. RESULTS: In Cx50D47A lenses, Cx50 levels were 11% (heterozygotes) and 1.2% (homozygotes), and Cx46 levels were 52% (heterozygotes) and 30% (homozygotes) when compared to wild-type at 2.5 months. Gap junctional coupling in differentiating fibers of Cx50D47A lenses was 49% (heterozygotes) and 29% (homozygotes), and in mature fibers, it was 24% (heterozygotes) and 4% (homozygotes) compared to wild-type lenses. Hydrostatic pressure was significantly increased in Cx50D47A lenses. [Ca(2+)](i) was significantly increased in Cx50D47A lenses. Alizarin red-stained calcium precipitates were present in homozygous Cx50D47A lenses with a similar distribution to the cataracts. CONCLUSIONS: Cx50D47A expression altered the lens internal circulation by decreasing connexin levels and gap junctional coupling. Reduced water and ion outflow through gap junctions increased the gradients of intracellular hydrostatic pressure and concentrations of free calcium ions. In these lenses, calcium ions accumulated, precipitated, and formed cataracts. These results suggest that mutant lens fiber connexins lead to calcium precipitates, which may cause cataracts.